On the stability of piecewise polynomial collocation methods for solving weakly singular integral equations of the second kind - Kangro, Raul; Kangro, Inga (Mathematical Modelling and Analysis, 2008)
Piecewise polynomial collocation methods on special nonuniform grids are efficient methods for solving weakly singular Fredholm and Volterra integral equations but there is a widespread belief that those methods are numerically unstable in the case of large values of the nonuniformity parameter r. We show that this method by itself is stable and discuss some implementation problems that may lead to unstable behavior of numerical results. First Published Online: 14 Oct 2010